Characterization of Two Urease-Producing and Calcifying Bacillus spp. Isolated from Cement - Achal, V.; Mukherjee, Abhijit; Reddy, M. (Han'gug Mi'saengmul Saengmyeong Gong Haghoe, 2010)
Two bacterial strains designated as CT2 and CT5 were isolated from highly alkaline cement samples using the enrichment culture technique. On the basis of various physiological tests and 16S rRNA sequence analysis, the bacteria were identified as Bacillus species. The urease production was 575.87 U/ml and 670.71 U/ml for CT2 and CT5 respectively. Calcite constituted 27.6% and 31% of the total weight of sand samples plugged by CT2 and CT5, respectively. Scanning electron micrography (SEM) analysis revealed the direct involvement of these isolates in calcite precipitation. This is the first report of the isolation and identification of Bacillus species from cement. Based on the ability of these bacteria to tolerate extreme environment of cement, they have potential to be used in remediating the cracks and fissures in various building or concrete structures.